PERFIL DAS DEMANDAS DAS FAMÍLIAS COM RESPONSABILIDADE FEMININA JUNTO AO PROGRAMA MINHA CASA MINHA VIDA 2 NA REGIÃO DOS CAMPOS GERAIS/PR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
This study aims to understand the demands of families with female responsibility with the Minha Casa Minha Vida 2 program, forcities with up to fifty thousand inhabitants, in Campos Gerais-PR region. For the development of this research, we assume that the housing issue is a major urban and social problems in Brazil, related to the right to housing, access to the city, as well as access to goods and services. The housing is provided by the Federal Constitution, in Article 6. Which guarantees the right to housing and thatit has decent living conditions. It is important to note that this study seeks to contextualize the Minha Casa Minha Vida 2, Under-50 program, because this federal government program has in its prioritizing parameters the families with the woman providing for the family. Thus, the universe of research is the the cities served by COHAPAR - Housing Company of Paraná - Regional Office of Ponta Grossa. Among the selected cities for the program, some are categorized as small cities II, these are: Arapoti, Imbituva, Jaguariaíva, Ortigueira, Piraí do Sul and Reserva. Professionals in charge of the Minha Casa Minha Vida 2 and with the Regional Office of COHAPAR were selected as subjects in this study. With an exploratory and descriptive nature, the research was carried out based on the following methodological instruments: documentary and bibliographical research, semi-structured interview, whose script was also used as an alternative to semi-structured questionnaire and systematization of the results of empirical and literature research. These results are organized into the following chapters: Chapter 1: Brazilian Housing Policy: overview and reflection on their social setting; Chapter 2: Socioeconomic Context of these cities: Arapoti, Imbituva, Jaguariaíva, Ortigueira, Pirai do Sul and Reserva, and the housing issue; Chapter 3: program Minha Casa Minha Vida 2, Sub-50 years old program: approaches demands identified in families with female responsibility.
Keywords: Políticas públicas de habitação; Programa Minha Casa Minha Vida; Família com responsabilidade feminina; Brazilian housing policy, Minha Casa Minha Vida Program; Family with female responsibility; CNPQ::CIENCIAS SOCIAIS APLICADAS